Prevalence and genetic characterization of viral gastroenteritis in hospitalized children aged <5 years in Yunnan Province, China, 2020–2022 - Li, Nan; Qiao, Enfa; Duan, Zhaojun; Li, Lili; Jiang, Lili; Cun, Jianping; Zhou, Xiaofang; Wang, Zhi Chao; Zhou, Yongming; Cao, Yihui (Frontiers in Pediatrics, 2025)
BackgroundRotavirus (RV), norovirus (NoV), human enteric adenovirus (HAdV), human astrovirus (HAstV), and sapovirus (SaV) are important viral causes of acute gastroenteritis (AGE) in children. However, limited information is available regarding AGE in Yunnan, Southwest China.MethodsTo investigate the prevalence of group A rotavirus (RVA), norovirus genogroups I (GI) and II (GII), and HAdV, HAstV, and SaV in children aged <5 years hospitalized with AGE between 2020 and 2022.ResultsStool samples were collected from 612 children hospitalized with AGE. A total of 266 of the 612 children presented with AGE (43.46%; 266/612). RVA was detected in 28.76% (176 of 612) of the children. Rotavirus G9P[8] was the most frequent genotype in 2020 and 2021. In 2022, G8P[8] became the dominant genotype combination circulating in Yunnan Province. The norovirus positivity rate was present in 11.93% (73/612) of the 612 samples. Of the 45 GII successfully sequenced samples, GII.4 was the dominant genotype, accounting for 51.11% (23 of 45), followed by GII.3 [P12] (28.89%; 13 of 45). The positivity rates for SaV, HAstV, and HAdV were 2.94% (18/612), 3.43% (21/612), and 4.74% (29/612), respectively. HAdV-F41 was the predominant genotype and non-enteric HAdV-C2 and HAdV-A12 were also observed in Yunnan. Male children had a higher incidence of AGE than female children upon infection with RV, NoV, and HAdV. The highest incidence of AGE was observed among children aged between 12 and 23 months (62.50%; 120/192), followed by children aged between 24 and 35 months (52.44%; 43/82). The incidence rate of the infection peaked (78.62%; 125/159) in the first 3 months of the year, followed by the next 3 months (66.67%; 70/105).ConclusionsRV and NoV remained the most important agents causing AGE. RV G8P[8] became the dominant circulating genotype instead of G9P[8] in Yunnan in 2022. The authors suggest that monitoring should be strengthened to prevent outbreaks caused by RV G8P[8]. New vaccines, such as the RV G8P[8] genotype, should be considered.